Interaction of glucokinase with the liver regulatory protein is conferred by leucine-asparagine motifs of the enzyme - Baltrusch, Simone (2005)
The glucokinase regulatory protein (GRP) plays a pivotal role in the regulation of metabolic flux in liver by the glucose-phosphorylating enzyme glucokinase. Random peptide phage display library screening for binding partners of GRP allowed the identification of an asparagine-leucine consensus motif. Asparagine-leucine motifs of glucokinase located in the hinge region, as well as in the large domain, were changed by site-directed mutagenesis. The L58R/N204Y and the L309R/N313Y glucokinase mutants showed a significantly reduced interaction with GRP. The L355R/N350Y mutant had a fivefold-higher binding affinity for GRP than wild-type glucokinase. Imaging of glucokinase and GRP fluorescence fusion proteins revealed that the L58R/N204Y glucokinase mutant lacked glucose-dependent translocation by GRP, whereas the L355R/N350Y glucokinase mutant was trapped in the nucleus due to high affinity for GRP. The results indicate that the L58/N204 motif in the hinge region confers binding to GRP, while the L355/N350 motif may modulate the binding affinity for GRP. This latter motif is part of the alpha10 helix of glucokinase and accessible to GRP in the free and complex conformation.